Magnetic Behaviour of Granular GdMnO3 Film - Negi, Puneet; Agrawal, H. M.; Singh, Jitendra Pal; Kumar, Hemaunt; Srivastava, R. C.; Asokan, K.; Chae, Keun Hwa (SPRINGER, 2017)
The present study deals with the investigation of magnetic properties along with morphological and microstructure analyses of a multiferroic GdMnO3 film fabricated on Si(100) substrate by the pulsed laser deposition technique. Rutherford backscattering spectroscopic analysis suggests that the film is fabricated in the form of diffused layers having different stoichiometric proportions. Raman spectroscopy signifies that few modes present in the film are associated with MnO6 octahedra and some extra peaks indicating the mixed phase formation in tuning with the Rutherford backscattering spectroscopy. Atomic force microscopy confirms the granular nature of the film. Field-cooled and zero-field-cooled thermal magnetization curves show irreversible behaviour extending well above room temperature, which is associated with spin disorder. The presence of Gd+3 state and Mn+3/Mn+4 mixed states in the uppermost layers of the film was confirmed by near-edge X-ray absorption fine structure. Subsequently, in association with these observations, the film is a weak ferromagnetic at 5 K and even at room temperature.
Keywords: X-RAY-ABSORPTION; PULSED-LASER DEPOSITION; THIN-FILMS; GROWTH